The influence of Castanea sativa Mill. flower extract on hormonally and chemically induced prostate cancer in a rat model. Issue 6 (1st March 2021) - Nascimento-Gonçalves, E.; Seixas, F.; Silva, M.; Fardilha, M.; Ferreira, R.; Neuparth, M. J.; Faustino-Rocha, A. I.; Colaço, B.; Venâncio, C.; Barros, L.; Ferreira, I. C. F. R.; Oliveira, M. M.; et al.
Abstract : Prostate cancer (PCa) is one of the most common cancers in men, with a huge impact on their health. Abstract : Prostate cancer (PCa) is one of the most common cancers in men, with a huge impact on their health. The use of Castanea sativa Mill. flowers (CFs) in beverages has been reported, through ancestral claims, as having health benefits. In vitro research has evidenced the properties of CFs, such as antitumor and antioxidant activities. This study aimed to evaluate the effects of CF extract in an animal model of PCa. Forty male Wistar Unilever rats were randomly assigned to four groups: control, induced, control + CF, and induced + CF groups. Animals from the induced groups were exposed to a multistep protocol for PCa induction. The CF extract, rich in trigalloyl-HHDP-glucoside and obtained via decoction, was administered to the CF groups in drinking water (3 mg per animal per day) for 49 weeks. Animals were sacrificed at 61 weeks of age. Regarding the effects of CFs on dorsolateral prostate tumorigenesis, no significant differences were observed between the induced and induced + CF groups. However, animals exposed to the CF extract showed fewer inflammation areas on the dorsolateral prostate lobe than those not exposed to CF. Moreover, the CF extract alleviated the hepatic oxidative stress associated with the multistep protocol, resulting in lower levels of lipid peroxidation. These results suggest that CF extract has antioxidant and anti-inflammatory properties.